Многофункциональная аппаратура передачи и приема данных З-501 - Kutsenko, V. N.; Levchenko, T. V. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
In operational remote-control systems, communication channels created by wired, VHF radio, radio relay, tropospheric, and space-based means are used, which operate under high interference conditions. A multifunctional data transmission and reception equipment Z-501 has been developed, intended both for voice communication and for transmitting information in the MTK-2 code via the specified communication channels, or for receiving such information with registration on a personal computer or on punched tape.